2018
DOI: 10.7577/hrer.2873
|View full text |Cite
|
Sign up to set email alerts
|

Hypocrites or heroes? Thinking about the role of the teacher in human rights education

Abstract: Human rights education (HRE) seeks to provide young people with an optimistic sense that we can work towards a more peaceful and socially just world, and that everyone can do something to contribute to securing improvement. But, whilst the academic literature and policy documents frequently position teachers as crucial to promoting human rights and social justice, the literature is also replete with examples of teachers' conservatism, their compliance in the face of authority and their ignorance. In addition, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 39 publications
(31 reference statements)
0
13
0
3
Order By: Relevance
“…Hvorvidt og hvordan kobles «verden der ute» til medborgerskap? Ulike fagdidaktiske refleksjoner og hensikter vil nødvendigvis utvikle forskjellige framstillinger, bilder og potensielt varierte forståelser av hvordan verden virker og endres, og påvirke elevenes syn både på verden og på sin egen rolle i utviklingen (Jerome, 2018;Saether, 2016;Vesterdal, 2016.) Denne artikkelen drøfter disse problemstillingene i lys av perspektivene til et utvalg samfunnsfaglaerere i videregående skole.…”
Section: Innledningunclassified
“…Hvorvidt og hvordan kobles «verden der ute» til medborgerskap? Ulike fagdidaktiske refleksjoner og hensikter vil nødvendigvis utvikle forskjellige framstillinger, bilder og potensielt varierte forståelser av hvordan verden virker og endres, og påvirke elevenes syn både på verden og på sin egen rolle i utviklingen (Jerome, 2018;Saether, 2016;Vesterdal, 2016.) Denne artikkelen drøfter disse problemstillingene i lys av perspektivene til et utvalg samfunnsfaglaerere i videregående skole.…”
Section: Innledningunclassified
“…These difficulties have been highlighted both in Scotland (BEMIS, 2013) and in other jurisdictions. Recent research has considered these problems: the general consequences and challenges of translation of the UNCRC into legislation in different jurisdictions (Robinson, Quennerstedt & I'Anson, 2020); developing a theoretical understanding of teachers' responsibilities in HRE (Robinson, Phillips & Quennerstedt, 2020;Jerome, 2018); translating human rights principles into classroom practices (Robinson, 2017). When we consider HRE, 13 current COVID 'recovery' efforts in schools and the extraordinary disruption of children's right to education during 2020 have significant implications (Magendzo and Osler, 2020).…”
Section: Opportunities and Future Directions For Human Rights Educationmentioning
confidence: 99%
“…Previous research has identified the teacher as a key actor for the performance of children's human rights learning in school-both when it is successful and when it is less so (Jerome, 2016(Jerome, , 2018Leung et al, 2011;Waldron & Oberman, 2016;Zembylas et al, 2017). For example, Leung et al (2011) have studied the development and implementation of a school-based HRE curriculum in Hong Kong.…”
Section: Human Rights In Educationmentioning
confidence: 99%